Technological advancement expands carbon storage in harvested wood products in Maine, USA. (June 2022) - Li, Ling; Wei, Xinyuan; Zhao, Jianheng; Hayes, Daniel; Daigneault, Adam; Weiskittel, Aaron; Kizha, Anil Raj; O'Neill, Shane R.
Abstract: Harvested wood products (HWPs) in-use, disposed to landfill, and the charcoal created by biomass fuel burning substantially store carbon and potentially mitigate the greenhouse gas effect. To quantify the HWPs carbon storage, we developed a carbon accounting framework, which has the ability to incorporate the influence of technological advancement on HWPs carbon storage. Through applying this framework together with the wood harvesting data of Maine, USA during the period of 1901–2019, we concluded that the current HWPs carbon pool size is 52 Tg C, which is 11% of the carbon stored in the entire forestry sector and wood products of Maine, USA. Technological advancement potentially increases the HWPs carbon storage by as much as 44% to 75 Tg C. In addition, the average net annual carbon sink can be increased from 0.44 Tg C to 0.63 Tg C. Production of innovative wood products with long service lives plays the most important role in expanding the HWPs carbon pool; however, the higher processing efficiency and recycling rate are less important. Graphical abstract: Image 1 Highlights: An advanced harvested wood products carbon accounting framework is developed. The current carbon storage in harvested wood products is 52 Tg C in Maine, USA. Innovative wood products effectively expand the carbon stored in harvested wood products.